Experimental and numerical investigation of perforated cold-formed steel built-up I-section columns with web stiffeners and complex edge stiffeners. Issue 10 (July 2019) - Wang, Chungang; Guo, Qinglin; Zhang, Zhuangnan; Guo, Yuting
A built-up I-section with web stiffeners and complex edge stiffeners is expected to have better performance to resist against local and distortional buckling compared to conventional built-up I-section. In order to study the influence of perforations on compression behavior of above section forms, a series of pin-ended compression tests and numerical analysis on perforated double-limb cold-formed steel built-up I-section columns with complex edge stiffeners and web stiffeners were conducted. The test specimens contained 12 concentrically loaded specimens and 8 eccentrically loaded specimens with two cross-section shapes, respectively. The test results were found that the web stiffeners could obviously increase the ultimate bearing capacity of the built-up members, especially for stub and medium-long columns. The ultimate bearing capacity of two cross-section shaped medium-long columns decreased gradually with the increase of eccentricity. Two adjacent single-limb webs of conventional built-up I-section could provide support to each other. The web stiffeners restricted the deformation of the plate around the holes effectively, but it also weakened the composite action between the single-limb webs. A finite element model was developed and verified against experiments of perforated built-up columns. Furthermore, a total of 96 parametric analyses were completed to investigate the optimal ratio of the hole depth to web sub-element in the Σ-shaped built-up I-section perforated columns. Finally, two types of direct strength method formulas were used to calculate the ultimate bearing capacity of perforated built-up specimens. The appropriateness of those direct strength method was compared. It was shown that the existing direct strength method formulas were both valid for perforated built-up I-section columns with complex edge stiffeners.